Hyperactivity and altered mRNA isoform expression of the Cl¯/HCO3¯ anion-exchanger in the hypertrophied myocardium - Chiappe de Cingolani, Gladys Ethel (2001)
Objective: The aim was to examine the regulation of the cardiac Na+-independent Cl¯/HCO3¯ exchanger (AE) mRNA isoform expression in association to the enhanced AE activity in the hypertrophied myocardium of spontaneously hypertensive rats (SHR). Methods: AE activity was determined by the initial rates of the pHi recovery from imposed intracellular alkalinization (forward mode of exchange) and the pHi rise induced by Cl¯ removal (reverse mode). Net HCO3¯ (JHCO3¯) efflux and influx were respectively determined. AE mRNA isoforms were analyzed by Northern blot with specific probes to detect AE1, AE2 and AE3 mRNAs. Results: Initial JHCO3¯ efflux after imposed alkaline load (pHi≅7.5) was higher in SHR than in normotensive WKY rats (3.01±0.33, n=7, vs. 0.64±0.29 mM/min, n=5, P<0.05). JHCO3¯ influx induced by Cl¯ deprivation was also increased in SHR, 4.24±0.56 mM/min (n=10) versus 2.31±0.26 (n=10, P<0.05) in WKY. In arbitrary units, the 4.1-kb AE1 mRNA decreased in SHR (0.15±0.01, n=7) compared to WKY (0.29±0.06, n=7, P<0.05), whereas the 3.6-kb mRNA did not change. AE2 mRNAs were similarly expressed in WKY and SHR. Cardiac specific AE3 (cAE3) mRNA decreased in SHR, 1.10±0.16 arbitrary units (n=8) versus 1.79±0.24, (n=8, P<0.05) in WKY. Full length AE3 (flAE3) mRNA increased from 0.69±0.06 (WKY, n=8) to 1.25±0.19 arbitrary units in SHR (n=8, P<0.05). Conclusions: The increase in flAE3 mRNA expression in cardiac tissue from the SHR is an adaptive change of the hypertrophied myocardium that might be in connection with the increased activity of the AE.